Adrenocortical Carcinoma Presenting with Signs of Acute Abdomen. (3rd February 2013) - Symeonidis, Dimitrios; Chatzinikolaou, Ioannis; Koukoulis, Georgios; Mamaloudis, Ioannis; Tepetes, Konstantinos
Abstract : Background . Adrenocortical carcinomas represent rare malignancies. In cases of hormone-secreting tumors, the hormone in excess determines the nearly diagnostic clinical presentation. Biologically inert tumors are diagnosed either due to the mass effect or incidentally. The purpose of the present study was to present an extremely rare presentation pattern of adrenocortical carcinoma. Case Presentation . We present the case of a 35-year-old female patient that underwent emergency laparotomy due to signs of acute abdomen and concomitant cardiovascular collapse caused by a spontaneously ruptured large adrenocortical carcinoma. Conclusion . Spontaneous rupture of an adrenocortical carcinoma presenting with signs of acute abdomen is an extremely rare clinical scenario. Increased level of suspicion is essential in order to diagnose and treat timely this life-threatening complication.